FAMILY VALUES IN THE PAINTINGS OF UZBEK ARTISTS (Academicia Globe: Inderscience Research, 2024)
The article is devoted to the theme of love, family and fidelity in the work of Uzbek artists. The theme of family values in Russian fine art has been and remains one of the main ones. The topic is relevant in the domestic mentality, where stories dedicated to marriage, motherhood and childhood became popular by the 17th century, in Uzbekistan it has always acquired a special flavor – despite social transformations and revolutions, and sometimes thanks to them.